Methods for the identification of important areas of plant diversity in Ireland - Walsh, Aidan (Trinity College (Dublin, Ireland). Department of Botany, 2016)
The loss of biodiversity is an on-going global issue that not only results in the extinction of species but also threatens the ecosystem services and goods on which humanity depends. The global community has responded with ambitious targets to halt and reverse the loss of biodiversity. The causes of biodiversity loss are well understood and conservation measures can be deployed to protect biodiversity. However, conservation resources are limited and to be effective must be targeted to the most important areas of biodiversity. Using vascular plant distribution records for Ireland this research examined the distribution of plant species of conservation concern to determine if additional conservation measures should be targeted to these species. In an attempt to aid the targeting of conservation measures to the most important areas of biodiversity this research also investigated methods for the identification of priority areas for plant conservation.
Keywords: Botany, Ph.D.; PhD Trinity College Dublin, 2016